Współczesna historiografia estońska - Mertelsmann, Olaf (Pamięć i Sprawiedliwość, 2010)
This paper aims at giving an overview on Estonian historiography on contemporary history since the regaining of independence in 1991. I will focus on authors living and working in Estonia, but have to mention also some research done abroad. With few exceptions, document editions and lists of victims of repression will not be dealt with. Because historians have not really started to investigate the 1990s, I will cover the period from establishing independence in 1918-1920 until the end of the Soviet regime. Different factors shaped the writing of history in Estonia in recent years. The Socialist past – Estonia was part of the Soviet Union as a Soviet republic – influenced greatly research on contemporary history. Professional history in Estonia was established by Baltic German scholars in the 19th century and Estonians entered the field as professional historians mainly in the interwar period, thus German and Soviet/Russian traditions were important. History is often seen as a ‘national science’ (rahvateadus) and an indivisible part of constructing national and state identity. Thus, many historians are on the track of a ‘national narrative’ of history. Additionally, Estonia is a small country with 1.3 million inhabitants, thus the community of historians is rather small, too. The brunch of quality research and publishing is conducted by a group of approximately 55 historians holding a PhD or the equivalent and not being retired yet. Most of the publications are in Estonian, but there is a growing trend to publish in English, Russian or German, too. The profession of historians faced like in other post-Socialist countries serious changes during transition. Some well-established Soviet historians lost influence and maybe their position. Others retired. The Soviet past had a serious impact, too. The distortion of history under Socialist rule led to the tendency since the late 1980s to explore the ‘blank spots’ of history in a certain positivist way stressing facts and not analysis, interpretation or a theoretical approach, but the further integration into European research structures has clearly a beneficent impact. Political history, the repressions under Stalin or military history seem to be at the moment far more important than let us say social or economic history. The main fields of interest remain the interwar period of independence, World War II and Stalinist rule, which have been presented in a rather distorted way by Soviet historiography.